2014
DOI: 10.1371/journal.pone.0100589
|View full text |Cite
|
Sign up to set email alerts
|

Photoactivated Localization Microscopy with Bimolecular Fluorescence Complementation (BiFC-PALM) for Nanoscale Imaging of Protein-Protein Interactions in Cells

Abstract: Bimolecular fluorescence complementation (BiFC) has been widely used to visualize protein-protein interactions (PPIs) in cells. Until now, however, the resolution of BiFC has been limited by the diffraction of light to ∼250 nm, much larger than the nanometer scale at which PPIs occur or are regulated. Cellular imaging at the nanometer scale has recently been realized with single molecule superresolution imaging techniques such as photoactivated localization microscopy (PALM). Here we have combined BiFC with PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 32 publications
2
67
0
Order By: Relevance
“…A full proof of this active configuration would require quantitative PALM imaging in multiple colors or atomic scale structural models of Ras/Raf dimers; neither is yet available. Nevertheless, using a combined BiFC and PALM approach (BiFC-PALM), we have recently shown that the complex between KRas G12D and the Ras binding domain of CRaf (Ras-GTP/CRaf-RBD) can further aggregate to form dimers and occasional higher order structures in cells (27). This observation suggests that tetrameric Ras/Raf complexes do exist under physiological conditions.…”
Section: Resultsmentioning
confidence: 99%
“…A full proof of this active configuration would require quantitative PALM imaging in multiple colors or atomic scale structural models of Ras/Raf dimers; neither is yet available. Nevertheless, using a combined BiFC and PALM approach (BiFC-PALM), we have recently shown that the complex between KRas G12D and the Ras binding domain of CRaf (Ras-GTP/CRaf-RBD) can further aggregate to form dimers and occasional higher order structures in cells (27). This observation suggests that tetrameric Ras/Raf complexes do exist under physiological conditions.…”
Section: Resultsmentioning
confidence: 99%
“…In order to generate high-resolution maps of specific protein-protein interactions, specific pairs of fragments have been identified for photoactivatable or photoswitchable proteins and used for imaging protein-protein interactions in superresolution [8689]. For example, a BiFC-PALM approach was recently developed using PAmCherry1 [88]. Nickerson et al .…”
Section: Resolving Biochemical Activities In Superresolutionmentioning
confidence: 99%
“…79 Recent dramatic advances in single molecule imaging techniques are giving us a deeper insight into interactions of Raf with Ras clusters. 81,82 Photoactivated localization microscopy with bimolecular fluorescence complementation (BiFC-PALM) allowing detection of protein-protein interactions with 18 nm precision was used to identify K-Ras/Raf clusters of 30 nm in diameter and to observe the nanoscale clustering and diffusion of these complexes from the cell membrane. 81 Similarly, quantitative PALM imaging has allowed visualization of Raf multimers.…”
Section: Ras Dimerization Oligomerization and Clusteringmentioning
confidence: 99%
“…81,82 Photoactivated localization microscopy with bimolecular fluorescence complementation (BiFC-PALM) allowing detection of protein-protein interactions with 18 nm precision was used to identify K-Ras/Raf clusters of 30 nm in diameter and to observe the nanoscale clustering and diffusion of these complexes from the cell membrane. 81 Similarly, quantitative PALM imaging has allowed visualization of Raf multimers. 82 This work suggests that the CAAX motif of Ras drives Raf molecules in clusters.…”
Section: Ras Dimerization Oligomerization and Clusteringmentioning
confidence: 99%